"That'S What We Call the Cocktail": Non-Opioid Medication and Supplement Misuse among Opioid Users. Issue 2 (April 2021) - Chatterjee, Avik; Lopez, Diego; Ramkellawan, Shankar; Brown, Rory; Smith, Kamala; Gaeta, Jessie M.; Baggett, Travis P.
Background: Recent evidence suggests that the practice of combining opioid use with non-opioid substances is common, though little is known about this phenomenon and how best to address it. Methods: We recruited adults in Boston, Massachusetts, with recent opioid use. We conducted semi-structured interviews to explore the practice of combining non-opioid substances with opioids and analyzed transcripts to identify themes. Results: Twenty-nine individuals completed interviews. Combining other substances with opioids was a well-known practice: "that's what we call the cocktail." Participants reported the use of clonidine, gabapentin, benzodiazepines, promethazine, amphetamine salts, quetiapine, barbiturates, cough and cold medications, as well as alcohol and candy in combination with opioids. Participants reported purchasing these substances on the street, stealing them, or getting them from a prescriber. Augmenting the opioid high was a common reason for combining substances. Importantly, participants also reported combining substances to treat psychiatric symptoms. Individuals commonly reported learning about combining substances "from people on the street" but also reported learning from the internet and television. Perceived benefits outweighed safety concerns. Participants also felt that using over-the-counter or prescription medications would be safe. Conclusions: Combining a variety of substances with opioids is common and driven by diverse motives. Clinicians caring for opioid-involved patients should consider screening for concurrent use of other substances and discussing the risks of this practice.